1998
DOI: 10.1161/01.hyp.31.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Excess for the Early Identification of Gestational Hypertension and Preeclampsia

Abstract: Abstract-We have examined prospectively whether the combined approach of establishing tolerance intervals for the circadian variability of blood pressure (BP) as a function of gestational age, and then determining the so-called hyperbaric index (area of BP excess above the upper limit of the tolerance interval) by comparison of any patient's BP profile (obtained by ambulatory monitoring) with those intervals provides a high sensitivity test for the early detection of pregnant women who subsequently will develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 37 publications
5
77
1
2
Order By: Relevance
“…While all these studies are based on ABPM done for 24 hours only, the most extended conclusion so far is that due to poor results in the diagnostic test based on the BP mean, ABPM does not provide a proper approach for the early identification of preeclampsia, and it should not be used in pregnancy. 11 Against the common approach of relying on the 24-hour mean of ABPM, the combined approach of establishing tolerance intervals for the circadian variability of BP as a function of gestational age 25 and then computing the hyperbaric index (area of BP excess above the upper limit of the tolerance interval) by comparison of any patient's BP profile with those intervals, has been shown to provide high sensitivity and specificity for the early detection of pregnant women who will have subsequent development of gestational hypertension or preeclampsia 12 as well as a proper approach for the prediction of the outcome of pregnancy. 26 Results from this trial on the impact of the duration and frequency of BP sampling on the reproducibility of mean values indicate that parameters calculated from the ABPM profile are much more dependent on duration of sampling than on sampling rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While all these studies are based on ABPM done for 24 hours only, the most extended conclusion so far is that due to poor results in the diagnostic test based on the BP mean, ABPM does not provide a proper approach for the early identification of preeclampsia, and it should not be used in pregnancy. 11 Against the common approach of relying on the 24-hour mean of ABPM, the combined approach of establishing tolerance intervals for the circadian variability of BP as a function of gestational age 25 and then computing the hyperbaric index (area of BP excess above the upper limit of the tolerance interval) by comparison of any patient's BP profile with those intervals, has been shown to provide high sensitivity and specificity for the early detection of pregnant women who will have subsequent development of gestational hypertension or preeclampsia 12 as well as a proper approach for the prediction of the outcome of pregnancy. 26 Results from this trial on the impact of the duration and frequency of BP sampling on the reproducibility of mean values indicate that parameters calculated from the ABPM profile are much more dependent on duration of sampling than on sampling rate.…”
Section: Discussionmentioning
confidence: 99%
“…10 Hypertensive patients, including women with gestational hypertension or preeclampsia, appear to have a greater day-to-day variability in BP than normotensive subjects. 23 Although most studies assessing the circadian BP profile have used 24-hour ABPM, as a compromise with practicality, monitoring over at least 48 hours has been shown to present advantages in the analysis of BP variability, 23,39 diagnosis of disease, 12,40 and evaluation of a patient's response to treatment. 39,40 The individualized estimation of rhythm characteristics become more reliable; new end points are obtained, such as the circadian period, which cannot usually be estimated from 24-hour records.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[10][11][12] Our research group showed first that HRV, BPV, and BRS are not changed in the second and third trimester in normal pregnancy. 10 In PIH and PE, an increased HRV and BPV, [13][14][15][16] and a decreased BRS 12 were described compared to healthy pregnant women, whereas other groups described no differences in those variability parameters in pre-eclamptic pregnancies. 17 The purpose of this study was to evaluate whether HRV, BPV, and BRS are different between various hypertensive disorders and in comparison to normal pregnancies.…”
Section: Introductionmentioning
confidence: 92%
“…Key Words: pregnancy Ⅲ preeclampsia Ⅲ blood pressure monitoring, ambulatory Ⅲ hypertension, pregnancy R ecent studies have tried to overcome the poor results from isolated blood pressure (BP) measurements in detecting hypertensive complications in pregnancy 1,2 by relying on ambulatory BP monitoring (ABPM). [3][4][5][6][7][8] Using this approach, a predictable trend of BP variation along pregnancy was demonstrated for normotensive pregnant women systematically monitored every 4 weeks from the first trimester of pregnancy until delivery. The trend of decreasing BP up to the middle of gestation followed by increasing BP up to the day of delivery could not be found in pregnancies complicated with gestational hypertension or preeclampsia.…”
mentioning
confidence: 99%